2022
DOI: 10.1177/21514593221113533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Femoral Neck Systems and Cannulated Cancellous Screws in Treating Femoral Neck Fractures: A Meta-Analysis

Abstract: Background We performed a meta-analysis to compare the efficacy and safety of the femoral neck system (FNS) with cannulated cancellous screws (CCSs) in treating femoral neck fractures (FNFs) in controlled clinical trials. Methods Eligible scientific articles published prior to September 2021 were retrieved from the PubMed, Web of Science, Springer, ScienceDirect and Cochrane Library databases. The statistical analysis was performed with RevMan 5.1. Results Seven retrospective studies met the inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Since Dr Smith-Petersen, an American physician, invented trifin screws for treating femoral neck fractures in 1931, femoral neck internal fixation surgical devices have been rapidly developed over the decades, and various internal fixation devices such as cannulated screws, DHS, proximal femoral locking plate, percutaneous compression plate, medial buttress plate, and FNS have been invented are used in clinical practice to this day. Among them, the novel FNS has obvious biomechanical advantages and can support the fracture in multi-axial direction, with excellent anti-rotation and anti-shortening properties, with significant clinical efficacy (15)(16)(17)(18)(19). However, in China, limited by unbalanced economic development, cannulated screw internal fixation is still the most important surgical method, especially in the vast Central and Western regions and primary hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Dr Smith-Petersen, an American physician, invented trifin screws for treating femoral neck fractures in 1931, femoral neck internal fixation surgical devices have been rapidly developed over the decades, and various internal fixation devices such as cannulated screws, DHS, proximal femoral locking plate, percutaneous compression plate, medial buttress plate, and FNS have been invented are used in clinical practice to this day. Among them, the novel FNS has obvious biomechanical advantages and can support the fracture in multi-axial direction, with excellent anti-rotation and anti-shortening properties, with significant clinical efficacy (15)(16)(17)(18)(19). However, in China, limited by unbalanced economic development, cannulated screw internal fixation is still the most important surgical method, especially in the vast Central and Western regions and primary hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…- ---------------------------------------------------------------------------------- shown that inverted triangular distribution has theoretically strong biomechanical properties and is the 'gold standard' for treatment with three cannulated screws (12,18,20,21). However, it must be emphasized that inverted triangular distribution has numerous shortcomings and limitations as well (15,16,(22)(23)(24). First of all, osteoporosis is common in elderly patients.…”
Section: Anesthesiamentioning
confidence: 99%
“…The additional anti-rotational screw accompanies the latter for increased rotational stability [5]. Within the last year, several meta-analyses have been published that compared the FNS and multiple cannulated screws [35][36][37][38][39]. The studies found less femoral neck shortening [36,38,39] and higher postoperative Harris Hip Score values [37][38][39] in patients treated with the FNS.…”
Section: Discussionmentioning
confidence: 99%